2006
DOI: 10.2174/138920206778604368
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Genes and Paths Involved in Alzheimers Disease: Using Gene Expression Profiles and Chemical Genetics at the Mouse Brain Level

Abstract: Gene expression profiling of a number of distinct brain regions under different behavioral and biological states was analyzed using DNA microarray technology. These included hippocampal development, aging process, environmental enrichment, fear conditioning, and calorie restriction. Our results identified numerous genes and signal pathways that may play critical roles in learning and memory, brain aging and longevity. Furthermore, chemical genetic approach combined with gene expression profiling analysis was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
(124 reference statements)
0
2
0
Order By: Relevance
“…DNA microarray technology is a useful tool to dissect the mechanism underlying brain dysfunction and ageing (Wu & Hu, 2006). To understand the molecular basis of neurodegenerative phenotypes, we have analysed the gene expression profiles in the brains of 3-and 10-month-old cDKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…DNA microarray technology is a useful tool to dissect the mechanism underlying brain dysfunction and ageing (Wu & Hu, 2006). To understand the molecular basis of neurodegenerative phenotypes, we have analysed the gene expression profiles in the brains of 3-and 10-month-old cDKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have demonstrated the essential role of the APOE gene (with the APOE4 allele increasing risk and the APOE2allele decreasing risk) both in familial late-onset and sporadic AD patients [12-15]. Different efforts have been made to identify others genetic factors involved in the pathophysiology of LOAD [16]. Association studies for specific candidate genes, selected because of their known biological function relevant to AD, have been performed for over 350 single nucleotide polymorphisms (SNP) of different genes including interleukin 1A (IL-1A), interleukin 1B (IL-1B), interleukin 1 receptor antagonist (IL-1RN) [17, 18], and methylentetrahydrofolate reductase (MTHFR) [19, 20].…”
Section: Introductionmentioning
confidence: 99%